Fossil Freshwater Fishes from the Pliocene of northern Colombia and the Palaeogeography of northern South America - Chaparro, Gustavo Adolfo Ballen; Montes, Camilo; Carrillo-Briceño, Jorge D.; Bogan, Sergio; Reinales, Sandra; Pinna, Mario C. C. de; Jaramillo, Carlos (Cold Spring Harbor Laboratory, 2024)
1 Abstract Freshwater fishes from northern Colombia are reported from the Sincelejo and Ware formations, of Pliocene age. A total of ten taxa have been identified comprising two orders, five families, and nine genera. Characters from dental morphology, fin spines, and cranial bones are provided as taxonomic tools for the study of fossil fishes. All of the taxa are members of groups currently restricted to drainages east of the Andes, suggesting that physical drainage connection was still present by the Pliocene between the Amazon-Orinoco and trans-Andean drainages such as the Magdalena-Cauca, or that these groups persisted in the trans-Andean region at least until Pliocene times. The genera Hemidoras , Serrasalmus , and Trachely-opterichthys are new records for the fossil fish fauna of South America. The genus Zungaro represents a new record for the trans-Andean region, whereas the genus Platysilurus is for the first time in Colombia. Most of these occurrences also represent the youngest occurrences in the fossil record. Literature records are reidentified as Pygocentrus from the La Venta fauna and the earily Oligocene in Peru. These assemblages suggest that the Sincelejo and Ware formations were deposited in rivers of large size that were part of a large drainage network connected to the Amazon-Orinoco despite being currently located west of the Andes. These findings suggest that the Cordillera Oriental and the Merida Andes were not dividing yet the drainage network in northern South America by the middle to late Miocene.